Analysis of threshold voltage variance in 45nm n-channel device using L27 orthogonal array method - Salehuddin F.; Mohd Zain A.S.; Idris N.M.; Mat Yamin A.K.; Abdul Hamid A.M.; Ahmad I.; Menon P.S. (2023)
In this research, orthogonal array of L27 in Taguchi Method was used to optimize the process parameters (control factors) variation in 45nm n-channel device with considering the interaction effect. The signal-to-noise (S/N) ratio and analysis of variance (ANOVA) are employed to study the performance characteristics of the device. There are only five process parameters (control factors) were varied for 3 levels to performed 27 experiments. Whereas, the two noise factors were varied for 2 levels to get four readings of Vth for every row of experiment. In this study, nominal-the-best characteristic was used in an effort to minimize the variance of Vth. The results show that the Vth values have least variance and percent different from the target value (0.287V) for this device is 1.42% (0.293V). This value is closer with International Technology Roadmap for Semiconductor (ITRS) prediction. © (2014) Trans Tech Publications, Switzerland.